2018
DOI: 10.1371/journal.pone.0199898
|View full text |Cite
|
Sign up to set email alerts
|

Climate-driven changes of riparian plant functional types in permanent headwater streams. Implications for stream food webs

Abstract: Little is known regarding consequences of climate change on riparian plant functional types (PFTs) related to leaf traits, with putative domino effects on stream food webs, plausible even if the tipping point of stream-desiccation is not reached. We hypothesized that, as stream food-webs are highly dependent on riparian subsidies, climate change might alter PFTs to the point of weakening terrestrial-aquatic linkages. We conducted a gradient analysis to assess the relative effects of climate, soil and riparian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 71 publications
2
13
0
1
Order By: Relevance
“…Our data revealed lower average nutritive value of the riparian foliage in warmer or in warm/semiarid zones. These results, together with other recent observations (e.g., Salinas et al 2018), support the notion that climate change can likely exacerbate the large dietary imbalance of stream detritivores (Cross et al 2005), either due to plant species turnover (interspecific variability) or phenotypic plasticity of species (intraspecific variability). However, results from our experiments did not support our hypothesis: the responses of feeding and growth rates, and assimilation, to changes in litter quality did not differ between populations of the three shredder species, and when exceptions did occur, these were most likely not due to local adaptations to use low-quality litter (discussed below).…”
Section: Discussionsupporting
confidence: 87%
“…Our data revealed lower average nutritive value of the riparian foliage in warmer or in warm/semiarid zones. These results, together with other recent observations (e.g., Salinas et al 2018), support the notion that climate change can likely exacerbate the large dietary imbalance of stream detritivores (Cross et al 2005), either due to plant species turnover (interspecific variability) or phenotypic plasticity of species (intraspecific variability). However, results from our experiments did not support our hypothesis: the responses of feeding and growth rates, and assimilation, to changes in litter quality did not differ between populations of the three shredder species, and when exceptions did occur, these were most likely not due to local adaptations to use low-quality litter (discussed below).…”
Section: Discussionsupporting
confidence: 87%
“…Experimental studies have found that elevated [CO 2 ] increases the C ∶ N ratio of tree leaves and causes greater accumulation of secondary chemicals (Stiling and Cornelissen 2007), which might adversely influence riverine shredders (Tuchman et al 2002). Further, gradient studies at regional (Chen et al 2013, Salinas et al 2018 and global (Yuan andChen 2009, Boyero et al 2017) scales predict that warming could significantly reduce leaf N and P (or just P). Some of these studies also point to warming-derived changes in other leaf traits of riparian vegetation, such as increasing silicon content and toughness (Boyero et al 2017, Salinas et al 2018, which can interfere with the feeding and digestive E-mail addresses: 3 encarnafenoy@ual.es; 4 fjmoyano@ual.es; 5 jjcasas@ual.es DOI: 10.1086/709023.…”
Section: Increased Atmospheric Carbon Dioxide Concentration ([Co 2 ])mentioning
confidence: 99%
“…Further, gradient studies at regional (Chen et al 2013, Salinas et al 2018 and global (Yuan andChen 2009, Boyero et al 2017) scales predict that warming could significantly reduce leaf N and P (or just P). Some of these studies also point to warming-derived changes in other leaf traits of riparian vegetation, such as increasing silicon content and toughness (Boyero et al 2017, Salinas et al 2018, which can interfere with the feeding and digestive E-mail addresses: 3 encarnafenoy@ual.es; 4 fjmoyano@ual.es; 5 jjcasas@ual.es DOI: 10.1086/709023. Received 15 June 2019; Accepted 26 November 2019; Published online 22 June 2020.…”
Section: Increased Atmospheric Carbon Dioxide Concentration ([Co 2 ])mentioning
confidence: 99%
“…Las fluctuaciones del nivel de agua de las lagunas, han dejado al descubierto, por tiempos prolongados, las zonas litorales de estos cuerpos de agua, afectando las condiciones naturales de los ciclos de vida de las plantas acuáticas (Villaroel et al, 2014). Esta transformación es aprovechada por las especies helófitas, las cuales toleran zonas de anegación, pero que en determinadas épocas del año pueden llegar a secarse por completo, ganando cada vez más el espacio de los litorales lacustres (Salinas et al, 2018).…”
Section: Discussionunclassified